2020
DOI: 10.1080/19420862.2020.1739825
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of therapeutic proteins by cation exchange chromatography-mass spectrometry and top-down analysis

Abstract: 2020) Characterization of therapeutic proteins by cation exchange chromatography-mass spectrometry and top-down analysis, mAbs, 12:1, 1739825, ABSTRACT Recently, cation exchange chromatography (CEX) using aqueous volatile buffers was directly coupled with mass spectrometry (MS) and applied for intact analysis of therapeutic proteins and antibodies. In our study, chemical modifications responsible for charge variants were identified by CEX-UV-MS for a monoclonal antibody (mAb), a bispecific antibody, and an Fc-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 78 publications
0
38
0
Order By: Relevance
“… 22 We have also performed peptide mapping and characterized the main proteoform in each CEX peak. 29 The potency measurements of the collected CEX fractions showed that the main CEX peak had a potency of 140%, while the CEX peak characterized as HC D102 isomerization only had a potency of 12–30%. 22 A potency of 98% was found for the second acidic peak on the CEX profile of antibody that mainly contains LC N30 deamidation.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“… 22 We have also performed peptide mapping and characterized the main proteoform in each CEX peak. 29 The potency measurements of the collected CEX fractions showed that the main CEX peak had a potency of 140%, while the CEX peak characterized as HC D102 isomerization only had a potency of 12–30%. 22 A potency of 98% was found for the second acidic peak on the CEX profile of antibody that mainly contains LC N30 deamidation.…”
Section: Resultsmentioning
confidence: 98%
“…CEX-UV was performed as described previously. 29 For peptide mapping, the SEC fractions were collected into an Eppendorf tube with the presence of 200 µL denature solution containing 6 M guanidine hydrochloride, 0.2 M Tris, 2 mM EDTA, and 20 mM methionine (pH 3.5) to minimize artificial oxidation caused by collection. SEC runs and fraction collection were carried out in triplicate.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fortunately, a combined top-down fragmentation and cation-exchange chromatography method coupled with mass spectrometry has been developed for the site-specific identification of chemical variants that result in charge differences, specifically methionine oxidation. Furthermore, this technology was applied to the analysis of a bispecific antibody [ 129 ]. One notable advantage of the top-down methodology is the reduced need for peptide mapping, which is a major drawback of previous strategies.…”
Section: Physical and Chemical Stabilitymentioning
confidence: 99%